Causes of School Dropouts among Congolese Muslim Refugees in Katwe, Kampala, Uganda - Mwisha Chinyabuuma; Amika A Wardana; Muhammad Abbas (Islam Realitas: Journal of Islamic and Social Studies, 2020)
Schools dropout is being a noticeable problem in Eastern Africa.  The school dropout fundamentally affected the future of children because it usually leads them to early marriage, drug use, hard work labor, and prostitution as the school dropout is being a serious issue in mostly Eastern Africa. This study is aimed at investigating factors contributing to the school dropout among Congolese Muslim refugee in Katwe, a village in Kampala.  Both qualitative and quantitative approach was used in this study in order to find out how language barriers and early marriages causes dropouts among Congolese Muslim refugees in Katwe; to examine how hidden costs at school causes dropouts among Congolese Muslim refugees in Katwe; and to determine the relationship between the causes of school dropout and the actual school dropout. The results of the current research show that 30% of respondents agree that language barriers are one of the most prevalent factors causes of school dropout in Katwe. The instable school fees and earlier marriage also were found as the contributed cause of school dropout. Alternative hypothesis that stated “there is a relationship between causes of school dropout and actual dropout among Congolese Muslim refugees in Katwe, Kampala, Uganda was adopted.Saat ini, putus sekolah merupakan salah satu permasalahan pelajar di wilayah Afrika Timur. Umumnya, pelajar yang putus sekolah adalah mereka yang miskin dan/atau yatim piatu serta tidak memiliki wali. Putus sekolah secara fundamental mempengaruhi masa depan anak karena situasi ini cenderung mendorong anak ke pernikahan dini, penggunaan obat-obatan terlarang, pekerjaan kasar, dan prostitusi. Berangkat dari fakta bahwa banyak pengungsi perkotaan Kongo yang putus sekolah, kami menyelidiki penyebab kondisi itu. Khususnya di Katwe, sebuah desa di Kampala, hambatan bahasa dan absennya biaya sekolah yang tetap di sekolah-sekolah terdekat diasumsikan sebagai penyebab utama kondisi putus sekolah para siswa pengungsi perkotaan Kongo di Katwe. Penelitian ini bertujuan untuk; mengetahui bagaimana hambatan bahasa dan pernikahan dini menyebabkan putus sekolah di antara pengungsi perkotaan Kongo di Katwe; untuk menjelaskan bagaimana biaya tersembunyi di sekolah menyebabkan putus sekolah di antara pengungsi perkotaan Kongo di Katwe; dan untuk menentukan hubungan antara penyebab putus sekolah di Katwe dengan putus sekolah yang sebenarnya. Penelitian ini menggunakan pendekatan kualitatif dan kuantitatif. Hasil penelitian ini menunjukkan sebesar 30% responden setuju bahwa hambatan bahasa adalah penyebab utama putus sekolah bagi pengungsi perkotaan Kongo di desa Katwe. Sebagai alternatif, penelitian ini mengadopsi hipotesis yang menyatakan bahwa “ada hubungan antara penyebab putus sekolah dan putus sekolah yang sebenarnya di antara pengungsi perkotaan Kongo di Katwe, Kampala, Uganda.